2011
DOI: 10.1038/ja.2011.90
|View full text |Cite|
|
Sign up to set email alerts
|

Total synthesis and absolute configuration of avenolide, extracellular factor in Streptomyces avermitilis

Abstract: The first total synthesis of extracellular factor, ''Avenolide'', in Streptomyces avermitilis has been achieved using a convergent approach. The stereogenic centers in two key segments were installed using Sharpless epoxidation and dihydroxylation. This synthetic study allowed the determination of the absolute configuration of avenolide as 4S,10R, and yielded important information on its structure-activity relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 26 publications
10
26
0
Order By: Relevance
“…4) confirmed that the natural compound has the absolute configuration of 4S,10R. The 4S,10S isomer possessed half the activity of the 4S,10R isomer, whereas the 4R,10R-isomer and 10-deoxy form (21) showed much reduced activity, suggesting that the 4S-absolute configuration and the presence of a hydroxyl group at C-10 are important for the binding to or signal perception by AvaR1.…”
mentioning
confidence: 76%
“…4) confirmed that the natural compound has the absolute configuration of 4S,10R. The 4S,10S isomer possessed half the activity of the 4S,10R isomer, whereas the 4R,10R-isomer and 10-deoxy form (21) showed much reduced activity, suggesting that the 4S-absolute configuration and the presence of a hydroxyl group at C-10 are important for the binding to or signal perception by AvaR1.…”
mentioning
confidence: 76%
“…A retro-synthetic strategy was pursued to allow for the production of avenolide from the convergent synthesis of three key fragments consisting of the iodide 11 , the aldehyde 12 and epoxy 10 (Figure 1C) following the reported protocol by Uchida et al 20 Starting from the commercially available 1-methyl-2-butene, a Sharpless asymmetric dihydroxylation 21 produced the diol intermediate 1 in 82% yield in a single step (Figure 1D). The desired key intermediates aldehyde 12 and iodo alkene 11 and epoxy 10 were also made following the same reported protocol except the use of TBDPS rather than TBS for improved reaction monitoring using TLC.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental procedures were adopted from the publication by Uchida et.al. 20 with further optimizations and modifications that have been stated. Detailed experimental procedures for relevant intermediates are specified in materials and methods section of supplementary information.…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about the biosynthetic pathways that elaborate butenolides, as opposed to canonical GBLs that can be produced enzymatically from commercially available precursors. To this end, we undertook a novel retro-synthetic strategy to afford the production of avenolide from the convergent synthesis of three key fragments consisting of the iodide 11, the aldehyde 12 and epoxy 10 ( Figure 1C) following the reported protocol by Uchida et al 20 Starting from the commercially available 1-methyl-2-butene, a Sharpless asymmetric dihydroxylation 21 produced the diol intermediate 1 in 82% yield in a single step ( Figure 1D). The desired key intermediates aldehyde 12 and iodo alkene 11 and epoxy 10 were also made following the same reported protocol except the use of TBDPS rather than TBS for improved reaction monitoring using TLC.…”
Section: Convergent Synthesis Of (4s 10r)-avenolide and Characterizamentioning
confidence: 99%
“…The experimental procedures were adopted from the publication by Uchida et.al. 20 This resulted in a simplified protocol for the synthesis of allyl alcohol 17 which otherwise was reported to be made in 2 additional reaction steps starting from epoxy 10 from. Acrylic group was added to ally alcohol 17 using DDQ by the reported procedure and followed by ring closing metathesis reaction to yield stereospecific (4S, 10R)-avenolide, 13.…”
Section: Total Synthesis Of Avenolidementioning
confidence: 99%